2009
DOI: 10.1111/j.1399-6576.2009.01981.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided technique allowed early detection of intravascular injection during an infraclavicular brachial plexus block

Abstract: The reported incidence of complications after peripheral nerve blocks is generally low and varies from 0% to 5%. The injuries related to brachial plexus block are perhaps more commonly reported, than after peripheral blocks of the lower extremity nerves. Recent reports suggest that expert ultrasound guidance may reduce but not completely eliminate complications as intraneural or intravascular injection. We report a case of accidental intravascular injection of local anesthetic during infraclavicular brachial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…83 In addition, ultrasound guidance is not immune to limitations of stimulation-based techniques, including intraneural and intravascular injection. 85,86 As a result of the dramatic shift toward direct ultrasound visualization, the focus and quantity of research devoted to nerve stimulation will likely diminish. However, numerous undeveloped and/or controversial issues remain and would benefit from further study.…”
Section: Future Directionsmentioning
confidence: 99%
“…83 In addition, ultrasound guidance is not immune to limitations of stimulation-based techniques, including intraneural and intravascular injection. 85,86 As a result of the dramatic shift toward direct ultrasound visualization, the focus and quantity of research devoted to nerve stimulation will likely diminish. However, numerous undeveloped and/or controversial issues remain and would benefit from further study.…”
Section: Future Directionsmentioning
confidence: 99%
“…In terms of complication avoidance, some case reports have demonstrated that the pressure applied with the ultrasound probe in the infraclavicular area can collapse blood vessels and lead to a negative aspiration test, even when needle position is actually intravascular [39]. …”
Section: Evidence Of Use Of Ultrasonography For Deep Nerve Blocksmentioning
confidence: 99%